Burden of Drug resistant Tuberculosis in newly diagnosed Tuber-culosis patients of Khyber Pakhtunkhwa, Pakistan - Abdul Jabbar; Taj Ali Khan; Hazir Rehman; Anwar sheed khan; Sajjad Ahmad; Sadiq noor Khan (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: To explore the burden of drug resistant tuberculosis in Khyber Pakhtunkhwa, Pakistan. Methods: A total of 8220 referred suspected TB patient samples were collected from 1st March 2016 to 28th February 2017 from TB laboratories across all districts of Khyber Pakhtunkhwa province and processed for the detection of drug resistant tuberculosis (DR-TB). Drug Susceptibility testing (DST) on all Mycobacterium tuberculosis complex (MTC) strains was performed at Provincial TB Reference Laboratory, Peshawar. Results: Among the 8220 suspected TB samples, 1351 samples were declared positive on culture. The DST results showed that 525 samples were resistant to at least one of the first and second line anti-TB drugs. Importantly, among these 525 TB resistance cases, XDR-TB were 0.4% (n=5), MDR-TB were 4.6% (n=62), polyresistant were 18% (n=243), monoresistant was 16% (n=215) and 61% (n=826) were reported as pan-sensitive. Gender wise ratio are slightly increased in female (n= 4230; 51.5%) as compared to male (n=3990; 48.5%), while the age group 15-24 were the main target of TB disease (n=1978; 24%). Conclusion: Our data suggests that DR-TB cases especially MDR-TB and XDR-TB in newly diagnosed TB patients are alarmingly increased in Khyber Pakhtunkhwa region. Furthermore, the timely detection of drug resistance is important to optimize treatment and management of MDR-TB as well as XDR-TB. Key words: Tuberculosis; MDR-TB; XDR-TB; Continuous....